Measuring the well-being of health care professionals in the Punjab: a psychometric evaluation of the Warwick-Edinburgh Mental Well-being Scale in a Pakistani population - Waqas,Ahmed; Ahmad,Waqas; Haddad,Mark; Taggart,Frances; Muhammad,Zerwah; Bukhari,Muhammad Hamza HB; Sami,Shahzad Ahmed; Batool,Sayyeda Mehak; Najeeb,Fiza; Hanif,Ayesha; Rizvi,Zehra Ali; Ejaz,Sumbul (PeerJ PrePrints, 2015)
Background: There is growing awareness of the public health importance of the mental well-being of population in general. This study was carried out to examine the wellbeing of Pakistani healthcare professionals, and to evaluate the psychometric properties of Warwick-Edinburgh Mental Well-being Scale in in this population. The well-being of health professionals is likely to influence their care delivery. Methods: A cross-sectional survey was carried out from June, 2013 to December, 2014 among 1271 Pakistani health personnel (HCPs) belonging to seven different cities of Punjab province, Pakistan, to examine the acceptability, internal consistency, test-retest reliability and the content and construct validity of the English version of the Warwick-Edinburgh Mental Well-being Scale in a Pakistani population sample. All data were analyzed in SPSS v.21. Results: Our analysis demonstrated a unidimensional construct, a high internal consistency (0.89) and test-retest reliability, good convergent validity and easy readability of WEMBS among Pakistani HCPs. The mean on WEMWBS score was 48.1 (9.4) which is lower than general population sample in other nations. Male healthcare professionals scored significantly higher on WEMWBS than their female counterparts (P < .05), and older respondents had higher scores. Conclusion: The WEMBS appears feasible and acceptable for use in the Pakistani healthcare professionals, and findings from this study indicate its validity and internal consistency. The well-being scores of the health professional respondents were lower than those identified in general population surveys in the UK.
Keywords: burnout; WEMWBS; Warwick-Edinburgh Mental Well-being Scale; mental fatigue; Health personnel; Mental health